1998
DOI: 10.1016/s0301-5629(98)00070-2
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock waves act by shock wave-gas bubble interaction

Abstract: Previous animal experimental data had su~ested that extracorporeal shock waves acted by the interaction of shock waves witi remnant gas bubbles Iefi horn eavitational activity from previous shocks (1). ht vitro experitnenk had shown that haemolysis frotn shock waves was reduced by >95 0/0by stitic express pressures of ody 10s kPa in the exposure vessel (2). Two additional experiments confiied the interaction. ht the fret, an identical number of 100 shock waves was administered slower than us~ly to red blood ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…The biological effect of the SW treatment on cells or tissues may be mediated by bubble-cavitation (23). The acoustic cavitation could induce membrane potential change as demonstrated in rat papillary muscle (24).…”
Section: Discussionmentioning
confidence: 99%
“…The biological effect of the SW treatment on cells or tissues may be mediated by bubble-cavitation (23). The acoustic cavitation could induce membrane potential change as demonstrated in rat papillary muscle (24).…”
Section: Discussionmentioning
confidence: 99%
“…In these applications, it is important and interesting to understand the behavior of a shock wave when it interacts with a small air bubble; for example, Delius et al [6] considered lithotripsy in vitro and concluded that the dominant mechanism of shock wave action on cells is shock wave-gas bubble interaction.…”
Section: Introductionmentioning
confidence: 99%
“…These holes are likely due to the shock wave-generated cavitation and to the mechanical stress produced by the pressure pulse. Delius, Ueberle, and Eisenmenger (1998) and Loske et al (2002) showed that there is synergy between shock waves and cavitation in the inhibitory effect observed after repeated application of ESW on eukaryotic cells and E. coli ATCC 10356, respectively.…”
Section: Discussionmentioning
confidence: 99%